Investigating the potential of diffusion tensor atlases to generate anisotropic clinical tumor volumes in glioblastoma patients - Kim Hochreuter; Gregory Buti; Ali Ajdari; Christopher P. Bridge; Gregory C. Sharp; Sune Jespersen; Slávka Lukacova; Thomas Bortfeld; Jesper F. Kallehauge (Physics and Imaging in Radiation Oncology)
Background and purpose:: Diffusion tensor imaging (DTI) has been proposed to guide the anisotropic expansion from gross tumor volume to clinical target volume (CTV), aiming to integrate known tumor spread patterns into the CTV. This study investigate the potential of using a DTI atlas as an alternative to patient-specific DTI for generating anisotropic CTVs. Materials and Methods:: The dataset consisted of twenty-eight newly diagnosed glioblastoma patients from a Danish national DTI protocol with post-operative T1-contrast and DTI imaging. Three different DTI atlases, spatially aligned to the patient images using deformable image registration, were considered as alternatives. Anisotropic CTVs were constructed to match the volume of a 15 mm isotropic expansion by generating 3D distance maps using either patient- or atlas-DTI as input to the shortest path solver. The degree of CTV anisotropy was controlled by the migration ratio, modeling tumor cell migration along the dominant white matter fiber direction extracted from DTI. The similarity between patient- and atlas-DTI CTVs was analyzed using the Dice Similarity Coefficient (DSC), with significance testing according to a Wilcoxon test. Results:: The median (range) DSC between anisotropic CTVs generated using patient-specific and atlas-based DTI was 0.96 (0.93–0.97), 0.96 (0.93–0.97), and 0.95 (0.93–0.97) for the three atlases, respectively (p > 0.01), for a migration ratio of 10. The results remained consistent over the range of studied migration ratios (2 to 100). Conclusion:: The high degree of similarity between all anisotropic CTVs indicates that atlas-DTI is a viable replacement for patient-specific DTI for incorporating fiber direction into the CTV.